Synthesis of Fluorine-Containing a-Acyloxycarboxamide Derivatives from Indane-1,2,3-trione, Isocyanides and 4-Fluorobenzoic Acid - Reza Kazemizadeh, Ali; Ramazani, Ali (Asian Journal of Chemistry, 2012)
Passerini reaction of indane-1,2,3-trione, isocyanides and 4-fluorobenzoic acid proceed at room temperature and the related fluorine-containing a-acyloxycarboxamide derivatives are synthesized in quantitative yields. The reactions are one-pot, single spot and the products were obtained without any purification.